Positive and Negative Personality Traits in Relation to Oral Health-related Quality of Life and Satisfaction After Implant-Supported Prosthetic Treatment - Hasheminejad, Naimeh; Farzadmoghadam, Maryam; Mohammadi, Mohammad; Nekouei, Amir; Rostamizadeh, Mohammadreza (Journal of Dentistry Indonesia, 2025)
Objective: This study aimed to determine patients’ positive and negative personality traits in relation to treatment satisfaction and oral health-related quality of life (OHRQOL) in patients who have received dental implant-supported prosthesis. Methods: This study was carried out on 135 adults above the age of 30 who had received reasonable implant treatment and prosthesis in the last 1–24 months in a private and a public dental office. Data collection was carried out using a questionnaire, which was sent to patients via WhatsApp and email. Also, the Persian version of the Oral Health Impact Profile 14 and the Positive Affect Negative Affect Scale were used to collect data related to OHRQOL and personality profiles. A Likert scale was also used to obtain the treatment satisfaction level. Results: Among 135 participants, most reported good oral hygiene and positive affect, with 62.7% rating their oral health as good and a mean PANAS score indicating an overall positive emotional state. Oral health-related quality of life was linked to tooth brushing and self-rated oral health, while satisfaction with implants was influenced by education and emotional affect. Conclusions: Overall, negative personality traits increased the chance of not being satisfied after an implant-supported prosthesis. Meanwhile, people with more positive personality traits had a better chance of being satisfied. Personality traits were not associated with OHRQOL.